THE INFLUENCE OF SERVICE QUALITY AND TICKET PRICE ON CONSUMER DECISIONS ON BUS PT. MEDAN NORTH STAR - Rodiatun Rodiatun; Muhammad Hilman Fikri (SEAN Institute, 2023)
This study aims to determine the effect of service quality and ticket prices on consumer decisions to use PT. North Star of Medan. The sample of this research is 100 consumers. The analysis technique used is Multiple Regression analysis, T test, F test and Coefficient of Determination. The suitability test using the t test was conducted to partially test the effect between the independent variable and the dependent variable with the assumption that other variables are considered constant. The results of the equation analysis. The calculated t value for the Service Quality variable (X1) is 13,434 when compared to the t table value of 1,660. Then the calculated t obtained is greater than the t table value or 13,434 > 1.660, then it is also seen that the sig value is smaller than the probability value 0.000 < 0.005 then Ho is rejected and Ha is accepted so that the X1 variable has a contribution to Y. The calculated t value for the Price variable Tickets (X2) are 4,177 when compared to the t table value of 1,660. Then the t arithmetic obtained is greater than the t table value or 4.177 > 1.660, then it is also seen that the sig value is smaller than the probability value 0.000 < 0.005 then Ho is rejected and Ha is accepted so that the X2 variable has a contribution to Y. The calculated f value is 828.061 with sig level 0.000 therefore sig value 0.000 <0.005 and F count 828.061> F table 2.70 this shows that Ho is rejected so it can be concluded that the independent variables X1, and X2 simultaneously have a positive and significant effect on the dependent variable Y. R square value (R2) or the square of R shows the coefficient of determination is 0.945 or 94.5%, meaning that the percentage of influence between Service Quality and Ticket Prices on Consumer Decisions. While the remaining 5.5% is explained by other factors.